Factors associated with hypertension among patients with type 2 diabetes: evidence from a resource-limited setting—Southern Ethiopia - Yakob, Begidu; Israel, Eskinder; Jaldo, Mesfin Menza; Abraham, Awoke; Yakob, Tagese (Frontiers in Endocrinology, 2025)
BackgroundGlobally, non-communicable diseases contribute to about three-quarters of all deaths. Developing nations face particular difficulties with the concurrent presence of diabetes and high blood pressure, problems intensified by poor nutrition habits, lack of physical exercise, and continuing high rates of illnesses like HIV/AIDS and malaria. A significant data gap in primary healthcare (PHC) data has been determined and prioritized by governments seeking to assess and enhance the prevention and management of chronic disease.ObjectiveThe main aim of the current study is to determine factors related to hypertension among patients with type 2 diabetes in public PHC facilities in Southern Ethiopia.MethodsA facility-based cross-sectional study was conducted from 6 March 2023 to 5 April 2023 among 409 patients with diabetes. A systematic random sampling technique was employed to select the study participants. The data were cleaned, coded, and entered into Epi-data version 4.6.0.2 and exported to STATA version 14 for analysis. For descriptive statistics, both bivariate and multivariable logistic regression analyses were employed. Variables with a p-value <0.05 in the multivariable logistic regression analysis were declared as significantly associated with outcome variables.ResultsA total of 407 patients with type 2 diabetes mellitus (T2DM) were included in the current study with a response rate of 99.5%, and the mean age of the study participants was 57.1 years (SD ±9.91). The prevalence of hypertension among patients with T2DM was 66.1% with a 95% confidence interval (CI) of 59.9–70.3. The age group of >60 years [adjusted odds ratio (AOR) = 2.09, 95% CI (1.02–4.28)], patients with ≥10 years’ duration of T2DM [AOR = 1.79, 95% CI (1.05–3.03)], body mass index ≥25 kg/m2 [AOR = 4.19, 95% CI (2.10–8.33)], and patients who have a family history of hypertension [AOR = 11.73, 95% CI (5.82–23.66)] were significantly associated with hypertension among patients with type 2 diabetes.ConclusionThe prevalence of hypertension is high and the majority has poor blood pressure control. Hence, DM care providers and other health sector stakeholders have to work in collaboration to prevent it by designing appropriate strategies especially for those at higher risk of developing hypertension.